Obtención de material compuesto de matriz de aluminio reforzado con grafeno mediante pulvimetalurgia (2019)
Several researchers have reported graphene as an ideal reinforcement for composite materials due to its interesting properties [1]. The graphene-reinforced aluminium matrix composite material was obtaining by powder metallurgy. This study investigated the effect of aluminum powder morphology on compaction capacity and mechanical strength of composite material. Different milling times were used to determine the optimal time required in manufacturing. The proper compaction load was determined change its values and analyzing the effect of the different loads on the characteristics of the composite. Sintering parameters were established according to previous studies employed by other researchers. Finally, it is determined that with 0.5% wt graphene presents phenomena of grain refinement and higher electrical conductivity of the compound with respect to powder metallurgical aluminum.